John Hejduk and Literature: From Retreat Masque to Architectural Requiem - Barberá Pastor, Carlos (Escritura e Imagen, 2024)
The architectural proposal developed by John Hejduk between 1980 and 2000 has ties toliterature, influenced by his wife, Gloria Fiorentino. The quotes and references in his drawings andsketches to literary works by authors such as Hawthorne, Flaubert, Hardy, Melville, Blanchot, Gide,Proust, Rilke, and Mann confirm these connections, stemming from the pleasure in reading that theAmerican architect expresses in his texts. This article aims to clarify these relationships between someof the New York architect’s works and literature. Although the connections with literary authors canbe defined in various aspects of his work, the relationships are intense from an overall perspective,encompassing two of his works, Retreat Masque and Architectural Requiem. The research workdevelops an analysis of some pieces that unravel these relationships between the two disciplines inan artistic sense. The relationships between the two disciplines and the link in a process of complexcorrelations are demonstrated.
Keywords: John Hejduk; Berlin Masque; Victims; Retreat Masque; Maurice Blanchot; Architectural Requiem